Курган раннього залізного віку біля Мотронинського городища - Могилов, О.Д.; Панченко, К.І.; Руденко, С.В. (Археологія і давня історія України, 2021)
Стаття присвячена публікації матеріалів передскіфського кургану 97 в околицях Мотронинського городища в Потясминні, що містив впускне скіфське поховання. In 2019, the Scythian Right-bank expedition organized by the Institute of Archaeology of the National Academy of Sciences of Ukraine and the National Historical and Cultural Reserve «Chyhyryn» excavated the barrows on the Motronyn hillfort suburb, located near Melnyky village, Chyhyryn district, Cherkasy Region, in the south of the Forest-Steppe of Dnieper Right-bank area. The barrows were erected in pre-Scythian Age and the barrow 97 also contained the inlet Scythian burial. This mound was 0.65 m high, the diameter was 8.8— 9.8 m. A pre-Scythian burial-memorial complex was discovered under the mound, destroyed by a later burial. Finds from it are represented by fragments of ceramic ware: pots, large earthenware pots, bowls, ladles. Some fragments are decorated with geometric patterns. Ceramic spindle whorls, iron knives, bronze arrowheads, plaques, and animal bones were also found. During the Middle Scythian period another deceased was buried in the center of the mound. The tomb had the shape of a rectangular pit, oriented along the west — east line. Its length was 1.89—2.16 m, width — 0.7—0.82 m, depth from the surface of the mound — 1.45 m. The skeleton laid supine, with its head to the west. The left leg was lying on a stone slab. A quiver with arrows was placed next to it. An iron sword and a knife with a bone handle were found near the belt. This burial was also accompanied with the laying of wares in the mound borders. A pot was buried in the north, and handmade and wheel-made bowls in the east. Pre-Scythian finds from the mound have analogies in different regions of the Ukrainian Forest- Steppe where antiquities of the Late Chornoliska and Zhabotyn cultures are widespread, in particular on the Middle Dniester and in the Southern Bug River region, on the Right-bank of the Dnieper and in the Vorskla River region. A set of pottery and an arrowhead of the Novocherkassk type allows us to date the mentioned assemblage by the second half of the 8th century BC. Funeral rite and grave goods of the Scythian Age burial also have parallels in the sites of that time, including the south of the Right-bank of Middle Dnieper. According to the pot type and arrowheads, this burial can be dated to the second half of the 6th century BC.